(untitled) (Konferensiyalar | Conferences, 2024)
Teachers are essential resources in education, serving as guides, mentors, and facilitators in the acquisition of knowledge and skills across all levels of learning. This study investigates into the multifaceted roles of teachers and their significant contributions to education, research, and knowledge dissemination. Utilizing data from the Global Innovation Index, the study also try to explored the performance of Uzbekistan across various pillars, including education, tertiary education, research and development (R&D), knowledge creation, impact, and diffusion. The findings reveal positive trends in knowledge creation and diffusion, indicating advancements in innovation within the country. However, challenges persist in certain areas, highlighting the need for continuous improvement and investment in education and research. Overall, this study highlights the critical role of teachers in driving innovation and fostering socio-economic development.